Non-targeted screening for novel psychoactive substances among agitated emergency department patients. (20th April 2016) - Lung, Derrick; Wilson, Nathan; Chatenet, Francois-Thibaut; LaCroix, Clemence; Gerona, Roy
Abstract: Context : Novel psychoactive substances (NPS) are being created and introduced at an unprecedented rate, causing frequent, large-scale epidemics. Current identification of NPS in clinical settings in the USA is limited to the retrospective case or small cluster analysis.Objective : The purpose of this study was to assess the utility of non-targeted comprehensive drug screening in the agitated patients in an emergency department (ED) setting.Materials and methods : This is a prospective, observational case series that was conducted in the ED of an urban Level I Trauma Center with an annual census of approximately 65, 000 patients per year. Since it is common clinical practice at this facility for haloperidol to be used as a second-line chemical restraint when initial dose(s) of benzodiazepines are deemed insufficient, we surmised that the subset of ED patients with psychomotor agitation severe enough to receive both these pharmaceuticals would be likely users of NPS. For 1 month, biweekly pharmacy medication audits identified 49 of these patients. There were sufficient, remaining blood samples from 23 of these patients for analysis. Serum from stored blood samples was analyzed using liquid chromatography-time-of-flight mass spectrometry (LC-TOF/MS; LC 1260, TOF/MS 6230, Agilent). Retrospective chart review was done to identify patient clinical information.Results : Six patient samples yielded seven different NPS: JWH-073, JWH-081, JWH-200, methylenedioxybenzylpiperazine, mephedrone, methoxetamine, and herkinorin.Conclusion : This study demonstrates that prospective, non-targeted NPS screening in a selected ED patient population is feasible and effective in identifying NPS.